Penerapan Evaluasi Pembelajaran Terhadap Peserta Didik di Sekolah Dasar - Lasrumata Ida Nababan; Annisya Ayu Sutrisna; Diandra Nazwa Aulia Ruswandi; Syahrial Syahrial (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
This study seeks to assess the assessment capabilities of students in our evaluation process conducted at SD Negeri 060852 Medan. It falls under the category of classroom action research, focusing on evaluating learning outcomes systematically to gauge achievement of predetermined educational goals. The objective is to gather data to measure student progress, development, and the effectiveness of teaching. Findings reveal that teachers at SD Negeri 060852 Medan implement evaluations following repeated lessons. Subsequently, they employ observational tools to guide students in self-discovery before providing explanations.